Mikropropagasi Tanaman Stroberi (Fragaria sp.) melalui Induksi Organogenesis - I MADE CHRISTIAN ADHI SAPUTRA; RINDANG DWIYANI; HESTIN YUSWANTI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2016)
Mikropropagation Plant Strawberries (Fragaria sp.) Through Induction of Organogenesis Problems for farmers strawberry in Bali are the difficulty of get healthy strawberries  seeds a with prices are relatively cheap. Micropropagation method is ways to multiplay seeds for solving the problem. Research aims to understand the influence of concentration ZPT NAA + BAP to organogenesis on explant leaves strawberries in vitro. Experiment arranged using a Randomized Block Design (RBD). Medium the base used is MS medium with adding of 2 gL- 1 of activated charcoal, and 0.1 ppm NAA. As the treatment is BAP with concentration of 5 ppm, 10 ppm and 15 ppm with 5 replications. The results showed that the use of 0,1 ppm NAA + 15 ppm BAP most effective in deflection (3,0 DAP) with the percentage of 90,00%. The use of the NAA 0,1 ppm + 15 ppm BAP also most effective in a time of swelling (7,6 DAP) with the percentage of 82,95 % , while only the use of the NAA 0,1 ppm + 5 ppm BAP that will be capable of eliciting shoots at 23 DAP time.